Cis and trans Isomers distinguished by imidazole N-alkylation after Debus-Radziszewski reaction starting from 2, 7-di-tert-butyl-pyrene-4, 5, 9, 10-tetraone. Issue 21 (27th May 2015) - Ma, Bin-Bin; Peng, Yu-Xin; Zhao, Pei-Chen; Huang, Wei
Abstract: We report the design and synthesis of three new imidazo[5, 4- f ]2, 7-di- tert -butyl-pyrene-imidazol derivatives prepared from 2, 7-di- tert -butylpyrene-4, 5, 9, 10-tetraone and respective aromatic aldehyde through Debus-Radziszewski reaction. It is noted that three pairs of cis and trans isomers (1 –6 ) can be separated after double imidazole N -alkylation for the central fused imidazole/pyrene/imidazole core, because of their distinguishable molecular polarity and improved solubility. Successful separation of every cis and trans isomeric pair can be verified by the single-crystal structural and spectral proofs. To the best of our knowledge, the current study is the first structural and spectral investigation on the imidazole N -alkylation of imidazole/pyrene/imidazole based compounds after successful separation of cis and trans isomers. Graphical abstract: Three pairs of cis and trans isomers with fused imidazole/pyrene/imidazole based compounds have been successfully separated after double imidazole N-alkylation, and they can be distinguished by 1H NMR spectra and X-ray single-crystal structures.